Characterization of alcohol polygenic risk scores in the context of mental health outcomes: Within-individual and intergenerational analyses in the Avon Longitudinal Study of Parents and Children. (1st April 2021) - Easey, Kayleigh E.; Wootton, Robyn E.; Sallis, Hannah M.; Haan, Elis; Schellhas, Laura; Munafò, Marcus R.; Timpson, Nicholas J.; Zuccolo, Luisa
Highlights: Alcohol PRS derived in the general population associated with consumption during pregnancy. Maternal alcohol PRS associated with perinatal depression at 32 weeks gestation. Maternal alcohol PRS associated with decreased offspring intellectual ability at age 13. Offspring alcohol PRS did not predict offspring alcohol consumption in adolescence. Abstract: Background: Heavy alcohol consumption often co-occurs with mental health problems; this could be due to confounding, shared biological mechanisms, or causal effects. Polygenic risk scores (PRS) for alcohol use can be used to explore this association at critical life stages. Design: We characterized a PRS reliably associated with patterns of adult alcohol consumption by 1) validating whether it predicts own alcohol use at different life-stages (pregnancy, adolescence) of interest for mental health impact. Additionally, we explored associations of alcohol PRS on mental health phenotypes 2) within-individuals (using own alcohol PRS on own phenotypes) and 3) intergenerationally (using maternal alcohol PRS on offspring phenotypes). We used data from the Avon Longitudinal Study of Parents and Children (ALSPAC) (n = 960–7841). Additional substance abuse behaviors and mental health/behavioral outcomes were investigated (alcohol phenotypes n = 22; health phenotypes n = 91). Findings: Maternal alcohol PRS was associated with consumption during pregnancy (strongest signal: alcohol frequency at 18 weeks' gestation: β = 0.041, 95% CI = 0.0.02–0.06), p = 1.01 × 10 −5, adjusted R 2  = 1.6 %), offspring alcohol PRS did not predict offspring alcohol consumption. We found evidence for an association of maternal alcohol PRS with own perinatal depression (OR  = 1.10, 95% CI = 1.02 to 1.18, p = 0.022) and decreased offspring intellectual ability (β=-0.209, 95% CI -0.38 to -0.04, p = 0.016). Conclusions: These alcohol PRS are a valid proxy for maternal alcohol use in pregnancy. Offspring alcohol PRS was not associated with drinking in adolescence. Consistently with results from different study designs, we found evidence that maternal alcohol PRS are associated with both prenatal depression and decreased offspring intellectual ability.